Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Dinas Perdagangan Dan Perindustrian Jombang - Nafiah, Ilmi; Anandita, Septian Ragil; Mahendri, Wisnu (CV. ITTC INDONESIA, 2022)
The research was conducted at the Department of Trade and Industry of Jombang Regency from May to August. The purpose of this final project is to determine the effect of discipline and work motivation on employee performance. The sample used in this study is as many as 65 respondents who have been determined using the saturated sampling technique. Measurement of employee performance using a questionnaire containing indicators of discipline and work motivation. Methods of extracting data by interview and observation, the data were analyzed descriptively to determine employee performance based on the variables of discipline and work motivation. Meanwhile, to find out the effect of the discipline variable and work motivation on employee performance using multiple linear regression analysis. Based on the research results obtained, it can be concluded that the performance of employees is included in the category of strongly agree. The results of multiple linear regression analysis can be seen that discipline and work motivation simultaneously (together), have a significant effect (Sig≤0.05) on employee performance. Partially, work discipline has a significant effect (Sig≤0.05) on employee performance, while work motivation has no significant effect (Sig>0.05) on employee performance.